Polyphenol characterisation and diverse bioactivities of native Australian lilly pilly (Syzygium paniculatum) extract. Issue 16 (27th July 2022) - Pachulicz, River J.; Yu, Long; Jovcevski, Blagojce; Bulone, Vincent; Pukala, Tara L.
Abstract : The magenta lilly pilly ( Syzygium paniculatum ) has been characterised as a high-yielding source of phenolic compounds, particularly anthocyanins, with the berry fruit extracts shown to have broad bioactivity of potential benefit to human health. Abstract : Magenta lilly pilly ( Syzygium paniculatum ) is an Australian native tree that produces berry fruits that are rich in phytochemicals reportedly beneficial to human health. Here we explored the biological activities of polyphenol-enriched extracts from the magenta lilly pilly fruit, benchmarking it against traditional sources including purple sweet potato and blackberry. We show that the extracts exert potent antioxidant and neuroprotective properties as well as antimicrobial activity against Staphylococcus aureus . The phenolic composition of lilly pilly was investigated using liquid chromatography coupled to mass spectrometry (HPLC-DAD-MS), revealing anthocyanins to be the primary component in high abundance compared to traditional anthocyanin-containing plants. Three anthocyanins from lilly pilly, along with their glycosylation patterns and stability, were characterised. Altogether, our results demonstrate the potential to exploit magenta lilly pilly fruits as a high-yielding source of phenolics with beneficial biological properties of potential interest for multiple downstream applications.